Riso, humor e racismo : narrativa de exclusão - Santos, Fabyanne Wilke Costa (2019)
This dissertation sought to understand the so-called "black people jokes", which were characterized as eloquent examples of racist humorous narratives. For this, the work is divided in three chapters. The first aimed to handle the phenomenon of humor and its conceptual understandings and considerations on the subject in contemporary times. And from this analysis were found points about the said inherent transgression of humor, as well as humor as a possibility of aggression. Then, it was asked about the possibility of understanding humor as a means of aggression. In an attempt to address this question, it was understood what Minois (2003) described about progressive laughter and conservative laughter, believing that the former aims to change social norms, while the latter is not intended for change, political reflection or social progress. However, Alberti (2002) believes that aggression and benevolence are concomitant with the laughable context. Therefore, for the author, every transgression would carry an aggression. Given the above, it was understood that the jokes that take as a laughing-stock a minority group, already socially fragile, such as the black people, gay, lesbian, woman, poor and others, would present themselves as eloquent examples of humor that is both aggressive and conservative. It was chosen as object of study, given the examples cited, the so-called "black people jokes", as well as in the universe of humor are called humorous narratives that take the object of mockery the black people. From this arose the need for the second chapter, with the intention of finding data on racism in Brazil and also to account for the links between humor and racism. From the data, it was noticed that Brazil is characterized by atypical actions of racism, which is structured from structural and symbolic attitudes of prejudice and discrimination. It is the so-called Brazilian racism. And, humor and the joke present themselves, as well as other informal narratives, as a pleasant form of prejudice, as they manage to surpass socially established norms and reaffirm the subjugated position of the black people, without being pointed as a discourse of racist intent. Finally, the third chapter presents a series of jokes that sometimes resemble the aggression and violence of racist discourse, sometimes present a certain denunciation of the existence of racism.